Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/jgs.16886
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Impact of FFC‐AL‐EIT on Psychosocial and Behavioral Outcomes in Assisted Living

Abstract: BACKGROUND This study tested the impact of Function Focused Care for Assisted Living Using the Evidence Integration Triangle (FFC‐AL‐EIT) on: (1) care interactions between residents and direct care staff; and (2) behavior and psychological symptoms associated with dementia among residents. DESIGN This was a randomized controlled trial. SETTING A total of 59 assisted living facilities in Maryland, Pennsylvania, and Massachusetts participated. PARTICIPANTS The sample included 550 mostly White (98%), female (69%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Regardless of whether the interventions aimed to stimulate positive social interactions ( 59 – 61 , 66 ) or empowerment ( 56 , 87 ), the fact that the focus was on the social aspects themselves and not on regular caregiving duties ( 63 , 68 , 75 ) provided structure to the social interactions. Socially oriented caregiving: Some interventions ( n = 6) described a shift from “passive” caregiving responsibilities to a more socially oriented approach ( 82 ) of enabling meaningful relationships to form between care staff and PLWD ( 63 , 68 ), encouraging openness in the dyadic relationship ( 84 ) and engaging PLWD in social interactions in the caregiving routine ( 75 , 82 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regardless of whether the interventions aimed to stimulate positive social interactions ( 59 – 61 , 66 ) or empowerment ( 56 , 87 ), the fact that the focus was on the social aspects themselves and not on regular caregiving duties ( 63 , 68 , 75 ) provided structure to the social interactions. Socially oriented caregiving: Some interventions ( n = 6) described a shift from “passive” caregiving responsibilities to a more socially oriented approach ( 82 ) of enabling meaningful relationships to form between care staff and PLWD ( 63 , 68 ), encouraging openness in the dyadic relationship ( 84 ) and engaging PLWD in social interactions in the caregiving routine ( 75 , 82 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, few included studies reported on interventions delivered in institutional settings adapting an activity or environment to support PLWD's participation in valued activities. Some examples were identified, such as creating a more responsive dining environment for dyadic interaction (88), story-telling groups (73), or educating staff to adapt and optimize interactions in caregiving (68,82,89). With research indicating that nursing home residents with dementia are involved in few social activities (99)(100)(101)(102), there is a need for more interventions to support "fine tuning" in formal caregiving to facilitate shared social activities that might enrich the caregiving dyad.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear, however, if function was optimized by engaging these individuals in bathing, dressing, and encouraging ambulation versus using a more task-focused approach and making sure that care tasks were provided (eg, that the resident was bathed and dressed). Although caregivers are concerned that encouraging function may exacerbate behavioral symptoms in this population, findings actually support the opposite 39. Interventions should continue to implement approaches to care that help optimize function in all individuals with moderate to severe dementia.…”
Section: Discussionmentioning
confidence: 98%
“…As the population ages, AL use is expected to grow (Sengupta et al, 2015). The goal of AL is to provide residential long‐term care for residents to age in place and to be as independent as possible for as long as possible, making it a unique setting distinct from the hospital or nursing home (Resnick et al, 2021). Consistent with the goal of promoting independence, leaders in AL research and practice have prioritized providing person‐centered care, including a focus on personhood, autonomy, and relationship‐based care practices (Zimmerman, Cohen, et al, 2014, Zimmerman, Allen, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%